Efficiency of Electrocoagulation, Sedimentation and Filtration Hybrid Process in Removing Chemical Oxygen Demand and Turbidity from Carwash Industrial Wastewater: Optimization by Response Surface Methodology - Mohammad Mahdi Emamjomeh; Hamzeh Ali Jamali; Zohreh Naghdali; Milad Mousazadeh (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Nowadays, rapid growth of car wash industries has led to a demand for wastewater reclamation. In this study, the hybrid process including electrocoagulation/flotation, sedimentation, and filtration were used in treatment of real carwash wastewater. Materials and methods: In this research, the sample was first entered into the ECF reactor, then entered the retention tank after specific times and eventually passed through filtration. COD was measured by closed reflux colourimetric method and turbidity was measured by Nephelometric method. To optimize the COD and turbidity removal efficiency, a central composite design was used based on response surface methodology (RSM) using Design-Expert version 7. Results: According to the the RSM model, optimum conditions for pH, electrolysis time, and applied current were 7.67, 1.69 amps and 90 min, respectively, in which COD removal and turbidity removal efficiency were 94.5% and 95%, respectively. The most predicted efficiency for the COD and turbidity removals were 100% and 96.69%, respectively. Electric energy consumption and operating costs were found to be 4.2 kWh / m3 and 8820 Rials, respectively. Conclusion: The hybrid treatment process used in this study, seems to be an efficient and cost effective method compared to existing conventional treatment methods used in removing pollutants from carwash wastewater. Therefore, this method can be used to remove pollutants with high concentrations from car wash industry wastewater and in wastewater reclamation.